Review of the Direct Laser Synthesis of Functionalized Graphene and its Application in Sensor Technology - Hyeong, Seok Ki; Choi, Kwang Hun; Park, Seoung Woong; Bae, Sukang; Park, Min; Ryu, Seongwoo; Lee, Jae Hyun; Lee, Seoung Ki (Applied Science and Convergence Technology, 2019)
Since the breakthrough in fabricating graphene by mechanical exfoliation in 2004, numerous methods have been developed to synthesize high-quality graphene materials on a large scale, including chemical exfoliation, thermolysis, and chemical vapor deposition. Recently, laser thermal treatments have emerged as facile methods for the direct synthesis of functionalized graphene materials, which show potential for use in a wide range of applications. The graphene materials produced by laser-based syntheses are classified by the fabrication method as either laser-reduced graphene or laser-induced graphene (LIG). The former is obtained through the chemical reduction of graphene oxide, while the latter utilizes the carbonization of a polymer precursor. In this review, we summarize the mechanisms of laser-assisted graphene syntheses, the structural and chemical functionalization of laser-scribed graphene, and various practical demonstrations of graphene-based materials in the field of mechanical and electrochemical sensors.
Keywords: Electrochemical sensor; Electromechanical sensor; Functionalization; Graphene; Laser ablation